Radiation response and combination target discovery in a novel model of rectal cancer - Beach, CJ (2024)
Rectal cancer is typically treated with radiotherapy, with or without chemotherapy, prior to surgical resection of the tumour. However, in patients that respond poorly to radiation, tumours largely lack significant immune cells within the surrounding milieu and present with a CAF-rich stroma. We have recapitulated this radioresistant phenotype in vivo through the implantation of Apcfl/fl, KrasG12D/+, Trp53fl/fl, TgfbrIfl/fl (AKPT) organoids. Here, through the irradiation of the heterotopic AKPT model, we have identified two targets for inhibition to augment the anti-tumour effect of radiation: complement C5a receptor 1 (C5aR1) and transforming growth factor beta (TGF-β).